MiR-34a Inhibits Viability and Invasion of Human Papillomavirus–Positive Cervical Cancer Cells by Targeting E2F3 and Regulating Survivin. Issue 4 (May 2015) - Geng, Dianzhong; Song, Xiaohua; Ning, Fangling; Song, Qianhua; Yin, Honghua
Abstract : Objective: Previous studies confirmed that high-risk human papillomavirus (HR-HPV) infection is a risk factor of cervical cancer, and the infection was associated with significantly reduced miR-34a expression during carcinogenesis. However, the downstream targets of miR-34a and their roles are still not well understood. This study explored the regulative role of miR-34a on E2F3 and survivin expression and the viability and invasion of HPV-positive cervical cancer cells. Methods: MiR-34a and survivin expression in 56 cases of HR-HPV–positive patients, 28 cases of HR-HPV–negative patients, and 28 normal cases without HR-HPV infections were measured. Human papillomavirus-18–positive HeLa cervical cancer cells and HPV-16–positive SiHa cells were used to explore the effect of miR-34a on cell viability and invasion. The molecular target of miR-34a was also explored in cervical cancer cells. Results: The results showed that miR-34a overexpression could inhibit HPV-positive cancer cell viability, whereas its downregulation promoted cell viability. E2F3 is a direct target of miR-34a in HPV-positive cervical cancer cells. By targeting E2F3, miR-34a could regulate the expression of survivin. Thus, through regulating E2F3 and survivin, miR-34a could reduce the viability and invasion of HPV-positive cervical cancer cells. Conclusions: This study confirmed a novel miR-34a–E2F3–survivin axis in the tumor suppressor role of miR-34a in cervical cancer.